The Impact of Personal, Family and Social Factors on Psychological Well-being of Patients with Breast Cancer to Develop a Structural Model - Maryam Soleyman Farokh; Ali Delavar (Hamadan University of Medical Sciences, 2020)
Introduction: Cancer is one of the most important diseases of the current century and the third leading cause of death after cardiovascular disease and accidents, and affects the psychological well-being of cancer patients. The aim of this study was to determine the effect of individual, family and social factors on the psychological well-being of patients with breast cancer in order to develop a structural model. Methods: The present study was descriptive in the form of structural equation modeling. Its statistical population consisted of all women with breast cancer being treated in medical centers and specialized hospitals for cancer in Tehran in the first quarter of 2019 (1350 people). The statistical sample was determined based on the research plan of 300 people and using multi-stage clustering method, clustering of medical centers based on geographical areas and then selection of a cluster was performed randomly. Data were collected using Reef's psychological well-being questionnaires, Baer et al.'s mindfulness, five neo-personality factors, Connor and Davidson's resilience, Ritchie and Fitzpatrick's family communication patterns, and Zymet's social support. Finally, the data were analyzed using multivariate linear regression test in the text of structural equation modeling and by AMOS software version 21. Results: The results of model analysis indicated that among the individual factors, the openness to experience, positively and neurosis has a negative effect on psychological well-being (P<0.01). Also, resilience and mindfulness have both positively increased mental well-being (P<0.01). In the case of familial factors and among the family communication patterns, the factor of orientation of conformity has reduced mental well-being (P<0.01). Finally, social support can increase psychological well-being (P<0.05). Conclusion: Thus, it can be acknowledged that, despite the difficult physical conditions that people with cancer face, it is possible to take appropriate social support to strengthen the resilience of these patients and finally, expect that the ability to adapt and cope with cancer will also increase in people with the disease.